Mental health and criminal justice - Segal, Anne F. (Mental health and criminal justice, 2019)
Introduction -- Mental health and criminal justice -- A brief history of mental illness -- The brain and the mind -- Etiology of mental illness -- First responders and street encounters -- Involuntary and voluntary commitments -- Legal competency and the criminal trial -- Mentally ill defendants: defenses, pleas, and verdicts -- Correctional treatment of the mentally ill -- Juveniles and mental illness: special considerations -- Mental illness issues in the community -- Justice for the mentally ill: human rights and at-risk groups